2020
DOI: 10.1080/20008198.2020.1815280
|View full text |Cite
|
Sign up to set email alerts
|

Association of traumatic stress and posttraumatic stress disorder with carotid atherosclerosis: findings from the general population

Abstract: Background: Cumulative evidence suggests that both traumatic stress and posttraumatic stress disorder (PTSD) are cross-sectionally and prospectively linked to cardiovascular disease (CVD). However, their association with proxy markers of atherosclerosis has hardly been investigated. Objective: The objective of this general population study was to relate traumatic stress and PTSD to carotid plaque and intima-media thickness (cIMT). Methods: 3119 adults from the general population were assessed regarding their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…For IMT, some studies have reported that PTSD is associated with higher IMT, yet findings are mixed and focused on male veterans or specific populations (eg, adults experiencing deportation). 42,43 Some studies have indicated associations of PTSD symptoms with WMH 44 and cognition, 45 yet these studies relied on data from males, veterans, and/or individuals undergoing PTSD treatment. The NHS II of midlife women found that women with histories of trauma exposure and more PTSD symptoms had greater declines in cognitive performance over approximately 1 year compared with women without PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For IMT, some studies have reported that PTSD is associated with higher IMT, yet findings are mixed and focused on male veterans or specific populations (eg, adults experiencing deportation). 42,43 Some studies have indicated associations of PTSD symptoms with WMH 44 and cognition, 45 yet these studies relied on data from males, veterans, and/or individuals undergoing PTSD treatment. The NHS II of midlife women found that women with histories of trauma exposure and more PTSD symptoms had greater declines in cognitive performance over approximately 1 year compared with women without PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior studies, largely focused on men and/or veterans, have considered PTSD symptoms in relation to cardiovascular or brain health. For IMT, some studies have reported that PTSD is associated with higher IMT, yet findings are mixed and focused on male veterans or specific populations (eg, adults experiencing deportation) . Some studies have indicated associations of PTSD symptoms with WMH and cognition, yet these studies relied on data from males, veterans, and/or individuals undergoing PTSD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…La actividad formativa y sus beneficios pueden abordarse como un valor afirmativo; los participantes egresados perciben que pueden tomar acciones cuando se requiere atender población en situación de trauma para contribuir activamente a la salud y el bienestar de las personas que atienden, lo que representa un efecto positivo considerando los problemas de salud asociados (Cavalcanti-Ribeiro et al, 2012;Cougle et al, 2009;Klest et al, 2013;Spitzer et al, 2020) y la grave interferencia en la vida cotidiana que se ha reportado (Adams et al, 2016;Bishop et al, 2017;McElroy et al, 2016). Los proveedores de atención para la salud y de atención de primera línea, necesitan implementar prácticas basadas en evidencia con sus pacientes a lo largo de un continuo de atención en diversos entornos (como hospitales y cuidados a largo plazo).…”
Section: Discussionunclassified
“…De manera más específica, los acontecimientos traumáticos han sido vinculados como un factor contribuyente para el desarrollo de problemas psiquiátricos, incluido el trastorno por estrés postraumático (TEPT), trastorno por estrés agudo (TEA), síntomas de disociación, depresión, abuso de sustancias, tendencias suicidas y conductas autolesivas, por mencionar las principales. También se le ha relacionado con problemas de salud física, como problemas isquémicos y conductas negativas para la salud, como fumar y obesidad (Cougle, Resnick y Kilpatrick, 2009;Klest, Freyd, Hampson y Dubanoski, 2013;Spitzer et al, 2020). Los efectos del trauma pueden incluir trastornos de la personalidad, relaciones interpersonales deterioradas, mal funcionamiento ocupacional y disminución de la calidad de vida (Cavalcanti-Ribeiro et al, 2012).…”
unclassified
“…Atherosclerosis and carotid plaques 19 [21,13,14,140,142,147,17,149,139,136,125,141,151,155,22,123,118] Arterial stiffness 3 [113,129,138] Arterial thickness 14 [135,148,137,114,115,133,124,119,144,126,121,130,156,153,122] Nonspecific cardiovascular risk factors 12 [146,112,114,115,145,131,116,150,120,143,134,127] Organ damage 1 [128] Not reported 1 [154] Technique Ultrasound 49…”
Section: Vascular Bed Assessedmentioning
confidence: 99%